THEORETICAL FOUNDATIONS OF SPORTS - Rajabova Mohinur Muzaffarovna (American Journals Publishing, 2023)
In this article, the objective state of sports theory is explained as a social phenomenon of the sphere of human activity, the system of conducting and organizing competitions, high sports results and victories in competitions, thereby strengthening health and conducting training sessions with the aim of general physical development of a person, being considered processes and manifestations of sports activities.
Keywords: sports, sports competitions, sports movement, sports activities, sports training, sports training system, sports school, sports training, athlete training, sports indicators, theory, sports theory.